Children and Online Game (Case Study of Simulation, Simulacra and Hyperreality in Children Playing Point Blank Game) - Panggio Restu Wilujeng (Berumpun: International Journal of Social, Politics, and Humanities, 2018)
This study aims to investigate children behavior in playing online games. This is qualitative study, case study, it was explored any behaviours of children online games activity with used participant observation, in depth interview and used snowball sampling as sampling technique. The theory used in this study is a theory of Simulation, Simulacra and Hiperreality by Jean Baudrillard that explain online games create condition, consequences or results from creation of reality models and imagination which replacing reality itself where children reality can replaced by game reality. . This Study located at Caesar Game Centre inside Kampung Ngoresan, most children plays in there. The result of this study shows different behaviours between each children on playing online games because of Simulacrum,built in Point Blank game then it blurred reality of children lifeworld in the game until Hiperreality shaped.